The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/pgpm.s231475
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Utility of CYP2C19 Genotype-Guided Antiplatelet Therapy in Patients at Risk of Adverse Cardiovascular and Cerebrovascular Events: A Review of Emerging Evidence</p>

Abstract: In patients undergoing percutaneous coronary intervention (PCI), the standard of care is dual antiplatelet therapy with a P2Y 12 inhibitor (clopidogrel, prasugrel, or ticagrelor) and aspirin. Current clinical practice guidelines now recommend more potent P2Y 12 inhibitors (prasugrel or ticagrelor) over clopidogrel in acute coronary syndrome (ACS). However, clopidogrel remains the most commonly prescribed P2Y 12 inhibitor in the setting of PCI and is also the preferred agent in the treatment and secondary preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…This treatment is widely used among the elderly and in persons with diabetes having a well-known high risk for cardiovascular diseases and increased platelet reactivity, i.e., secondary prophylaxis in cerebral infarction and acute coronary syndrome, respectively [ 3 , 5 , 6 , 7 ]. The treatments have been shown to inhibit blood clots in coronary artery disease, peripheral vascular disease and cerebrovascular disease, and to prevent myocardial infarction [ 3 , 8 , 9 ]. Although clinical practice guidelines now recommend prasugrel and ticagrelor over clopidogrel, in acute coronary syndrome patients undergoing percutaneous coronary interventions (PCI), clopidogrel remains the most widely used P2Y12 inhibitor [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This treatment is widely used among the elderly and in persons with diabetes having a well-known high risk for cardiovascular diseases and increased platelet reactivity, i.e., secondary prophylaxis in cerebral infarction and acute coronary syndrome, respectively [ 3 , 5 , 6 , 7 ]. The treatments have been shown to inhibit blood clots in coronary artery disease, peripheral vascular disease and cerebrovascular disease, and to prevent myocardial infarction [ 3 , 8 , 9 ]. Although clinical practice guidelines now recommend prasugrel and ticagrelor over clopidogrel, in acute coronary syndrome patients undergoing percutaneous coronary interventions (PCI), clopidogrel remains the most widely used P2Y12 inhibitor [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatments have been shown to inhibit blood clots in coronary artery disease, peripheral vascular disease and cerebrovascular disease, and to prevent myocardial infarction [ 3 , 8 , 9 ]. Although clinical practice guidelines now recommend prasugrel and ticagrelor over clopidogrel, in acute coronary syndrome patients undergoing percutaneous coronary interventions (PCI), clopidogrel remains the most widely used P2Y12 inhibitor [ 3 , 9 ]. Clopidogrel is a prodrug that requires cytochrome P450 biotransformation, primarily by CYP2C19, to form an active metabolite that selectively and irreversibly inhibits the purinergic P2Y12 receptor and, thus, platelet aggregation for the life span of the platelet [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the genotype-based strategy in prescription of P2Y12-inhibitors lowers the risk of high on-platelet reactivity and MACE. 39 Currently the genotype-based strategy in the prescription of P2Y12-inhibitors is only recommended in patients at high risk of thrombotic events and not suitable for all comers as the trials have shown the conflicting results. 40 There is an unmet need for a novel complex biomarker that can combine genetic profile and platelet laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, numerous observational studies have shown that CYP2C19 no function allele carriers prescribed clopidogrel after PCI have higher rates of major adverse cardiovascular and cerebrovascular events (MACCE) compared to patients with no function alleles treated with prasugrel or ticagrelor. 4,7 CYP2C19 genotype-guided P2Y12 inhibitor selection after PCI, wherein patients with no function alleles are prescribed prasugrel or ticagrelor, has been increasingly adopted to guide treatment of patients undergoing PCI. 8,9 The average age of patients undergoing PCI has increased from 2003 to 2016 with about half of patients currently being over 65 years of age.…”
Section: Introductionmentioning
confidence: 99%